Vanadium-free NASICON-type electrode materials for sodium-ion batteries. Issue 41 (13th October 2022) - Wu, Yechao; Meng, Xianhe; Yan, Lijing; Kang, Qiaoling; Du, Huiwei; Wan, Chubin; Fan, Meiqiang; Ma, Tingli
Abstract : Sodium-ion batteries (SIBs) have been rapidly developed as an effective replacement or supplement for lithium-ion batteries (LIBs) due to the high natural abundance and low cost of sodium resources. Abstract : Sodium-ion batteries (SIBs) have been rapidly developed as an effective replacement or supplement for lithium-ion batteries (LIBs) due to the high natural abundance and low cost of sodium resources. Sodium super ion conductor (NASICON)-type materials have high ionic conductivity and excellent structural stability, making them one of the potential electrode candidates for SIBs. V(vanadium)-based polyanionic compounds have been the most extensively studied NASICON-structure materials. However, the environmental pollution and high-cost issues of V-based materials demand serious consideration. Currently, V-free NASICON-type electrodes have garnered a lot of attention. In this review, V-free NASICON electrodes for SIBs are first systematically summarized. The latest advances in related cathode/anode materials with various metal redox couples are classified and introduced in terms of their preparation method, structural characteristics, and electrochemical performance. Moreover, the performance improvement strategies and future prospects are discussed. It is expected that the insights may inspire future research into the development of more clean, efficient, and low-cost electrodes for SIBs.